EPIDEMIOLOGY OF FASCIOLOSIS IN NILI RAVI AND KUNDI BUFFALOES AND ITS EFFECT ON HEMATOLOGICAL PARAMETERS (Journal of Medical & Health Sciences Review, 2025)
Fasciola hepatica is a common parasite of grazing livestock. Fasciolosis is a burning problem for the livestock and dairy industry in Pakistan. The coproscopic examination was done for fasciolosis and associated risk factors were explored in Nili Ravi and Kundi buffaloes from various dairy farms in the locality of district Mardan. For this purpose, a total of 450 buffalo communities were chosen for random research faecal and blood sampling. A subset of 450 (N=450) buffaloes from these farms were divided into 2 groups based on species. Group A (n = 225) Nili Ravi, and Group B (n = 225) Kundi. 5grams of fecal material collected from each individual and tightly packed in a polyethylene bags in the month of September 2023. After proper collection of samples, it was stored in refrigerator at 4C till processing. All the groups examined in the laboratory one by one carefully by using dissecting microscope in the Lab of laboratory of Clinical Medicine and Pathology in the month of September to October 2023. From the current research work district Mardan KP, showed overall 38% (171/450) incidence rates. Out of which 20% were Nili-Ravi and 18% were Kundi Buffalo. The site which favors more prevalence was Khaow 56.14% and lowest Toru 16.4% the most hygienic habitat. During copro-scopic study two species of Fasciola name F.hepatica and F.gigantica and their eggs were identified using Medical Parasitology key. Blood sample was collected in EDTA tube. Positive cases analyzed in a hygienic laboratory. Hematological parameters were checked in infected buffalo then compared to healthy one. The changes recorded shown significant reduction in various blood cells count. The proposed framework applied and evaluated on two buffalo breeds, namely, Nili Ravi and Kundi. At the end of study, statistical analysis applied on collected data such as percentile, ANOVA and t-test will be applied on prevalence, risk factors analysis and blood parameters respectively. The result should be made correct significantly at (P